2008
DOI: 10.1088/0022-3727/41/14/144017
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of molecular absorption cross-sections in mercury plasmas at very high pressures using self-reversed line diagnostics

Abstract: Plasmas containing mercury at pressures >100 bar are used as sources of extremely high radiance. High-resolution measurements have been made of the absolute spectral radiance of a plasma in a line of sight through its centre. Detailed comparisons of the Hg 546 nm calculated line shape with measurements provide information about the pressure, centre temperature and the temperature profile. Results are given for an arc at a pressure of 160 ± 10 bar and maximum temperature of 8350 ± 100 K. Radiation transport cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…This pressure range has been confirmed by measurements of n and T on the axis 10 ͑with n from the width of the 1014 nm Hg line 19 ͒ and recently also at the wall ͑with n from a Brewsterangle measurement 6 ͒. A lower pressure ͑16 MPa͒ has been estimated by Wharmby,20 but for a nonstandard experimental lamp and with a less direct method. In spite of the successful pressure measurements in single lamps, 6,19 the existing techniques are quite complex as to measurement and analysis and thus of limited use as standard methods in industry.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…This pressure range has been confirmed by measurements of n and T on the axis 10 ͑with n from the width of the 1014 nm Hg line 19 ͒ and recently also at the wall ͑with n from a Brewsterangle measurement 6 ͒. A lower pressure ͑16 MPa͒ has been estimated by Wharmby,20 but for a nonstandard experimental lamp and with a less direct method. In spite of the successful pressure measurements in single lamps, 6,19 the existing techniques are quite complex as to measurement and analysis and thus of limited use as standard methods in industry.…”
Section: Introductionmentioning
confidence: 56%
“…This is especially interesting for the 1014 nm Hg line 10,19 at higher pressures ͑25-30 MPa͒ and for the near-UV and blue Hg lines. 20 The present experiment could still be improved in several respects. First, ⌬ can be measured more accurately than here ͑2%͒.…”
Section: Discussionmentioning
confidence: 82%
“…These figures show that the oscillations which start to occur around b ¼ 50 arise when the line profile is dominated by the Levy contribution. Wharmby 23 already mentioned that impact and quasistatic theory have their limitations and that for high densities the Levy profile can cause unrealistically large red wings. He was still able to obtain accurate results by convolving again with a Gaussian profile to artificially limit these wings.…”
Section: Numerical Stabilitymentioning
confidence: 99%
“…In a previous paper [8] we treated a pure mercury Hg lamp, and it was demonstrated that, assuming a temperature profile derived from experimental measurements (Bartels' method [9], from spectral analysis of the Hg 577 nm line) the numerical model successfully reproduced the observed Hg spectra. Wharmby [10] has noted that Bartels' method was an appropriate tool to derive the gas temperature in the 1950s, before the ready availability of computers. However, he recommended that the numerical technique described here should replace Bartels' method to compute the temperature profile.…”
Section: Introductionmentioning
confidence: 99%
“…Bartels' method requires a number of quite restrictive assumptions [11] with limited ranges of validity, whereas numerical integration of line radiation is only dependent on the knowledge of the line broadening coefficients. For a more detailed discussion of these issues, the reader is referred to [10,11].…”
Section: Introductionmentioning
confidence: 99%